Analysis Of Improvement Student Knowledge Using Video Tutorial Media Through The YouTube Application On Class XI Culinary Pastry Material At SMKN 9 Padang - Barus, Anisa Devita Boru; Andriani, Cici; Elida, Elida; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
The development of science and technology has affected various aspects of life, including education. One aspect that has developed is learning media, with video tutorial media being an effective and interesting tool, especially in the culinary field. Video tutorials allow students to learn material visually and can be accessed at any time, facilitating independent learning. This study aims to determine the effect of using video tutorial media through YouTube in improving student knowledge on pastry material in class XI Culinary SMKN 9 Padang. The research method used was an experiment with a pretest-posttest control group design. The research sample consisted of 64 students, with 32 students in the experimental class XI Culinary 4 and 32 students in the control class XI Culinary 2. Data collection techniques include tests and documentation, while data analysis uses normality, homogeneity, and hypothesis tests with independent sample t-test. The posttest t-test results show that the knowledge value of experimental and control class students has a tcount value of 3,227> ttable 1,99897 or sig. (2-tailed) 0,021 < 0,05. Thus, Ho is rejected and Ha is accepted, which means there is a significant difference in the value of student knowledge between classes that use video tutorials via YouTube and classes that use conventional learning media.